Seberapa Efektif Kualitas Auditor yang Memoderasi Hubungan Antara Rasio Keuangan dan Kesulitan Keuangan - Tomy Rizky Izzalqurny (Jurnal Akuntansi, 2021)
This study aims to find out the influence of financial ratios toward financial distress in the further period, and the quality of auditors can reduce the influence of low financial ratios toward financial distress in the further period. The population of this study is manufacturing companies that have reviewed the 2016 and 2017 financial statements.In the selection of research samples using a purposive sampling method, in the order, the research sample numbered 137 firm years. The dependent variable is financial distress. Independent variables are divided into three variables of profitability, leverage, and liquidity. The moderating variable is the quality of the auditor. In this study hypothesis testing using the moderated regression analysis (MRA) model which includes using a tiered regression analysis method. This study provides evidence that the financial distress in the next period is influenced by profitability and leverage, and not prove that financial distress in the next period could be moderated by the quality of auditors.